The Baptismal Covenant and the Proposed Anglican Covenant - Meyers, Ruth A. (Journal of Anglican studies, 2011)
An exploration of the development and meaning of the text of the Baptismal Covenant in the 1979 Book of Common Prayer of the Episcopal Church provides the basis for a discussion of the proposed Anglican Communion Covenant. The article concludes by suggesting how biblical, theological and liturgical understandings of covenant offer a perspective by which to assess the proposed Covenant for the Anglican Communion.